Usulan Penurunan Tingkat Kecacatan Produk Pelat Baja dengan Metode Six Sigma - Muhamad Bob Anthony (Universitas Serang Raya, 2017)
This study aims to maximize the decline in the level of product defects to lead to zero defects. Researchers use the six sigma method through 5 stages of completion, namely, define, measure, analyze, improve, and control. Based on the results of the study it can be concluded that the sigma level and the value of DPMO (Defect per Million Opportunities) of the company amounted to 3.47 with possible damage of 24,239 sheets for one million productions. After further analysis using the Pareto diagram, it found that the cutting fault transfer defect was the most common with a percentage of damage of 43%. And based on the results of the analysis of fishbone diagrams, it can be seen that the main factors causing contamination in the production process come from the worker factor (human), followed by machine factors, material, and work methods. The proposed improvements that can be made by the company include updating existing methods and SOPs (standard operating procedures) and monitoring the operator's performance and developing knowledge and planning proper maintenance scheduling.